Fatigue damage accumulation of details in cars according to criterion of specific energy of total strain - Kulichenko, A. Ya.; Kuzin, N. O.; Vakulenko, L. I. (Science and Transport Progress, 2013)
Purpose. Modern ideas about the accumulation of fatigue damages in the details of railway vehicles are based on models that estimate the durability of metal systems and depend on the number of cycles and the magnitude of deformations or stresses. These models allow one to assess with a sufficient degree of adequacy the weakening of metal systems in polycyclic fatigue and at the presence of the elastic strain only in the details of rolling stock. However, the possibility of plastic deformation appearing during operation of rail transport structures is not taken into account. The aim of this work is a construction of a mathematical model that allows estimating the durability of metal systems with regard to the appearing of the plastic component in the process of deformation of parts of railway vehicles. Methodology. With the use of modern methods of solid mechanics the influence of the parameters of plastic deformation on the durability of highly loaded structural elements was analyzed. Findings. The effect of elastic and plastic deformation on the energy dissipation under cyclic loading was studied. Originality. It was shown analytically that the softening parameters of metal systems are related to the total energy of deformation, which characterizes features of the degradation processes in the metal structures under external loads. Practical value. Ratios were proposed, they allow estimating residual life of details in a sequential multilevel cyclic loading.